Comparison of Injury Severity Score (ISS) and New Injury Severity Score (NISS) in the Evaluation of Thoracic Trauma Patients: A Retrospective Cohort Study - He Jin; Yuanyuan Zhang; Qi Zhang; Lijuan Ouyang; Xueyao Li; Yiyan Zhang; Baosheng Yang; Junfeng Sun; Chaohui Wei; Guimei Yang; Li Guan; Shilan Luo; et al. (Emergency Medicine International)
Objective. To explore the value of the injury severity score (ISS) and the new injury severity score (NISS) for evaluating injuries and predicting complications (pneumonia and respiratory failure) and poor prognoses (in-hospital tracheal intubation, extended length of hospital stay, ICU admission, prolonged ICU stay, and death) in patients with thoracic trauma. Methods. The data of consecutive patients with thoracic trauma who were admitted to the department of cardiothoracic surgery of a tertiary hospital between January 2018 and December 2021 were retrospectively collected. ISS and NISS were calculated for each patient. The study outcomes were complications and poor prognoses. The differences in ISS and NISS between patients with complications and poor prognoses and patients without the abovementioned conditions were compared using the Mann‒Whitney U test. Discrimination and calibration of ISS and NISS in predicting outcomes were compared using the area under the receiver operating characteristic (ROC) curve (AUC) and Hosmer‒Lemeshow (H-L) statistic. Results. A total of 310 patients were included. ISS and NISS of patients with complications and poor prognoses were greater than those of patients without complications and poor prognoses, respectively. The discrimination of ISS in predicting pneumonia, respiratory failure, in-hospital tracheal intubation, extended length of hospital stay, ICU admission, prolonged ICU stay, and death (AUCs: 0.609, 0.721, 0.848, 0.784, 0.763, 0.716, and 0.804, respectively) was not statistically significantly different from that of NISS in predicting the corresponding outcomes (AUCs: 0.628, 0.712, 0.795, 0.767, 0.750, 0.750, and 0.818, respectively). ISS showed better calibration than NISS for predicting pneumonia, respiratory failure, in-hospital tracheal intubation, extended length of hospital stay, and ICU admission but worse calibration for predicting prolonged ICU stay and death. Conclusion. ISS and NISS are both suitable for injury evaluation. There was no statistically significant difference in discrimination between ISS and NISS, but they had different calibrations when predicting different outcomes.